Sunan Drajat’s Influences to Islamic Education: 15th Century - Mukhlis, Fahrudin (Pendidikan Agama Islam, 2019)
This paper attempts to provide a brief history of the nine saints named by walisongo, and more specifically Sunan Drajat and his role in the development of Islamic Education in various fields, such as da'wah, social, arts and culture and purification of aqīdah or creed. Specifficaly, this article will depict some points, such: First, the roles of Wali Songo to the propagation of Islam in Java; Second, Sunan Drajat’s method in Educating people; Third, Sunan Drajat’s Influences to Islamic Education. These aspects which give a description of a very good and successful method of preaching Islam in Indonesia especially in the land of Java